Bonjour ,et ce que vous pouvez m'aidez s'il vous plait?
Question
2 Réponse
-
1. Réponse maudmarine
Bonjour,
A = (7 - 3x) (9x - 3)
A = 63x - 21 - 27x² + 9x
A = - 27x² + 63x + 9x - 21
A = - 27x² + 72x - 21
B = (- 2 - 3y) (4 - 8y)
B = - 8 + 16y - 12y + 24y²
B = 24y² + 16y - 12y - 8
B = 24y² + 4y - 8
C = (4a + 6) (- 3 - 5a)
C = - 12a - 20a² - 18 - 30a
C = - 20a² - 12a - 30a - 18
C = - 20a² - 42a - 18
D = (5z - 7) (8z + 2)
D = 40z² + 10z - 56z - 14
D = 40z² - 46z - 14.
-
2. Réponse Skabetix
Bonjour,
[tex](7 - 3x)(9x - 3)[/tex]
[tex] = 63x - 21 - 27 {x}^{2} + 9x[/tex]
[tex] = - 27 {x}^{2} + 72x - 21[/tex]
[tex]( - 2 - 3y)(4 - 8y)[/tex]
[tex] = - 8 + 16y - 12y + 24 {y}^{2} [/tex]
[tex] = 24 {y}^{2} + 4y - 8[/tex]
[tex](4a + 6)( - 3 - 5a)[/tex]
[tex] = - 12a - 20 {a}^{2} - 18 - 30a[/tex]
[tex] = - 20 {a}^{2} - 42a \: - 18[/tex]
[tex](5z - 7)(8z + 2)[/tex]
[tex] = 40 {z}^{2} + 10z - 56z - 14[/tex]
[tex] = {40z}^{2} - 46z - 14[/tex]